Offstage Whitman in His Final Years: A Review of Brenda Wineapple’s Walt Whitman Speaks - Sueyoshi, Kiyotaka (AMERICANA E-journal of American Studies in Hungary, 2019)
Walt Whitman Speaks: His Final Thoughts on Life, Writing, Spirituality, and the Promise of America as Told to Horace Traubel Brenda Wineapple New York: Library of America, 2019. 130 pages eISBN 978–1–59853–615–7